A biomechanical comparison of midshaft clavicle plate fixation between two screws and three screws on each side of the fractures - Naufal Ranadi Firas; Erwin Ramawan (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
ABSTRACT The operative management of mid-clavicle fractures with plate and screw fixation is often performed, with either two or three screws on each side of the fracture. This research aimed to compare biomechanical stability on plate and screw fixation of the middle clavicle fracture with two screws and three screws on each fracture side. There were 12 samples of the fractured cadaveric clavicle in the middle and divided into two treatment groups. The first treatment group was given plate fixation and two screws on each side of the fracture, the second treatment group with plate fixation and three screws. Each group was given a repetitive load tensile force of 200 N, and the fracture shift was measured every ten times, 20 times, and 50 times. The statistical analysis showed a significant difference between plate fixation with two screws and three screws on the tensile force's repetition 20 times and 50 times. The lowest average displacement value after repetition of tensile forces is found in fixation with three screws. Biomechanically, the plate fixation system with three screws on each fracture side was more stable than the two screws in the middle clavicle fracture fixation.Keywords:            biomechanics, clavicle fracture, plate, screwCorrespondence:       nau.orthobaya@gmail.com